2015
DOI: 10.12911/22998993/59355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treated Sewage Outflow From a Modernized Sewage Treatment Plant on Water Quality of the Breń River

Abstract: Human economic activity and increasing urbanisation are among the main reasons of worsening the quantitative and qualitative state of surface waters. The rate and scale of resulting anthropogenic changes more and more frequently exceed the natural processes occurring in the environment. The outcome of the changes may be either a deficit or excess of water and pollution of extensive areas, which very often are difficult to reverse [Kanownik and Rajda 2011a, Kanownik

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…The results described by Kowalik et al (2015) are quite different from those obtained by this work. They determine the effect of treated sewage discharged from a mechanical-biological sewage treatment plant, modernized in 2007-2008, on the water quality of the Breń River.…”
Section: Discussioncontrasting
confidence: 98%
“…The results described by Kowalik et al (2015) are quite different from those obtained by this work. They determine the effect of treated sewage discharged from a mechanical-biological sewage treatment plant, modernized in 2007-2008, on the water quality of the Breń River.…”
Section: Discussioncontrasting
confidence: 98%
“…The load of supplied sewage proved too big in relation to water flow in the stream, which led to worsening of water quality in the watercourse. Also, research conducted by KOWALIK et al [2015] on the Breń River revealed a considerable influence of treated sewage discharge from modernized mechanical and biological sewage treatment plant on the quality of receiving waters. The discharge caused increase in values of 12 out of 17 analysed physicochemical indices in the Breń River, of which in 8 cases these dependencies were statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, studies by Ofman et al [2017] showed that properly treated sewage does not affect the quality of receiving waters. The results of research by Kowalik et al [2015] show that although the discharge of treated sewage to one of the rivers of the southern Poland caused a statistically significant increase in half of the tested physicochemical indicators of the receiving waters and the change in the water quality class from I to II, the concentrations of pollutants in the treated sewage did not exceed the limit values specified in the water law permit. Wąsik et al [2017] showed, however, that although most of the tested physicochemical parameters allowed for the classification of the treated sewage-receiving river to I or II class of water quality, microbiological contamination expressed by the numbers of coliforms and Escherichia coli classified the quality of the river below the point of sewage discharge even to IV and V class.…”
Section: Introductionmentioning
confidence: 97%